Wound Vitality in Decomposed Bodies: New Frontiers Through Immunohistochemistry - Bertozzi, Giuseppe; Ferrara, Michela; La Russa, Raffaele; Pollice, Giovanni; Gurgoglione, Giovanni; Frisoni, Paolo; Alfieri, Letizia; De Simone, Stefania; Neri, Margherita; Cipolloni, Luigi (Frontiers in Medicine, 2021)
Background: The question about wound vitality and the estimation of wound age of production are two of the classic investigation fields of forensic sciences. To answer this, the techniques most frequently used in research studies are immunohistochemistry (IHC), molecular biology, and biochemistry. Despite the great data on the literature about the usefulness of IHC in forensic pathology, there is always a request for further studies, especially on tissues altered by putrefactive phenomena. In fact, the degradation of the tissues is intended as the main limiting factor to the use of this technique. Scope: The aim of this pilot study was to evaluate the immunohistochemical behavior of samples collected from decomposed bodies (in different putrefaction phases) and to relate these findings to wound vitality and postmortem interval. Materials and Methods: Samples of skin and soft tissues were collected during autopsies, which were executed on decomposed bodies, whose cause of death was concluded to be traumatic. An immunohistochemical study was performed using antibodies against CD15, CD45, IL-15, tryptase, and glycophorin-A MMPs (endopeptidases involved in degrading extracellular matrix proteins: MMP-9 and MMP-2). An immunohistochemistry (IHC) reaction was evaluated according to a qualitative method as the following legend: (0): not expressed, (+): isolated and disseminated expression, (++): expression in groups or widespread foci, and (+++): widespread expression. Results: Most of the tested markers (tryptase, glycophorin, IL15, CD 15, CD 45, and MMP9) showed to be highly expressed in the tissue of putrefied skin for 15 days. Discussion and Conclusion: Although certainly inconclusive, this experimental application demonstrated that a nonexclusive but combined use of multiple antibodies is appropriate to verify wound vitality in decomposed bodies. Among them, GPA exhibited major reliability.